Karakterisasi Plasma Nutfah untuk Perbaikan Varietas Kedelai Sayur (Edamame) - nFN Asadi (Buletin Plasma Nutfah, 2009)
Edamame or vegetable soybean is one of the most important vegetable particularly in Japan, Taiwan, China and Korea. In Edamame quality is measured based on six criteria: appearance, taste, flavor, sweetness, texture, and nutritional value. Since 1998 the conservation and characterization of edamame germplasm have been done at Indonesian Center of Agricultural Biotechnology and Genetic resources Research And Development (ICABIOGRAD), and since 2007 research program breeding edamame have been started. The research is a collaboration with Asian Vegetable Research and Development Center (AVRDC). The research results showed: (1) edamame is potential to be developed in Indonesia, (2) based on morphological, agronomical characterization and organoleptic testing on 34 accessions of edamame germplasm were found those 10 accessions have gray pubescence, 22 accessions produced medium seeds (20-<30 g/100 seeds), 6 accessions produced the large seed (>30 g/100 bijou), 14 accessions had good taste, good seeds and pods performance, (3) based on 5 crossing combinations were obtained 20-200 F1 seeds. The F1 seeds were planted and will be developed to find selected edamame lines as candidate edamame release varieties, (4) edamame lines introduction from Taiwan were adapted well in Pacet (West Java, 900 m above sea level). AbstrakEdamame atau kedelai sayur (vegetable soybean) merupakan jenis sayuran yang sangat populer di Jepang, Taiwan, Cina, dan Korea. Ada enam kriteria yang menentukan kualitas edamame, yaitu penampilan, rasa, bau, tingkat kemanisan, tekstur, dan nilai gizi. Sejak tahun 1998 BB-Biogen (dulu Balitbio) telah memulai kegiatan konservasi, karakterisasi, dan plasma nutfah edamame. Pada tahun 2007 telah dimulai kegiatan pemuliaan yang bekerja sama dengan AVRDC. Hasil penelitian menunjukkan bahwa (1) edamame berpotensi untuk dikembangkan di Indonesia; (2) dari 34 aksesi yang telah dievaluasi dan karak-terisasi telah diperoleh 10 aksesi berbulu abu, 22 aksesi berbiji sedang (20-29 g/100 biji), 6 aksesi berbiji besar (>30 g/100 biji), 14 aksesi memiliki rasa enak dan penampilan polong rebus bagus; (3) dari 5 kombinasi persilangan yang dibuat telah diperoleh 20-200 biji F1 untuk diseleksi lebih lanjut; dan (4) galur edamame introduksi dari Taiwan beradaptasi dengan baik di Pacet (Jawa Barat pada ketinggian 900 m dpl).